Effect of rain & haze on availability of terrestrial free space optical link under tropical weather conditions - Basahel, Ahmed; Islam, Md. Rafiqul; Ahmad Zabidi, Suriza; Habaebi, Mohamed Hadi (IEEE, 2016)
Availability is a major concern to measure the QoS of Free Space Optical (FSO) communication link. In tropical areas, rain is the most dominant factor affecting the FSO link availability; whereas haze has no significant impact on FSO link availability compare to rain. In this paper,availability assessment of FSO was examined based on predicted atmospheric attenuations due to rain and haze. The predicted atmospheric attenuations due to rain and haze were obtained using rain rate (mm/hr) and visibility (km) data measured in Malaysia. The effect of individual weather phenomena was analyzed and availability performance of FSO was evaluated. Combine effect of both rain and haze was also demonstrated using cumulative distribution function (CDF) of both atmospheric attenuations due to rain and haze. This study provides recommendations to FSO researchers in general and local telecom service provider in particular about possible availability figures that can be useful for deployment of FSO system over one kilometer link distance.